Nitridation-Etch of Silicon Oxide in Fluorocarbon/Nitrogen Plasma: A Computational Study - Du Zhang; Yu-Hao Tsai; Hojin Kim; Mingmei Wang (Journal of Microelectronic Manufacturing, 2019)
The continually increasing number of silicon oxide (SiO2) and nitride (Si3N4) layers in 3D-NAND offers both motivations and challenges for developing all-in-one plasma etch solutions for etching SiO2 and Si3N4 at a selectivity near unity while maintaining a high etch rate. This is essential for a simultaneous etch landing of all holes that differ in their respective SiO2 and Si3N4 layer numbers and dummy SiO2 thickness, and for a quick wafer turnover. Surface modification may be employed to make the SiO2 and Si3N4 layers closer in composition, either by converting Si3N4 to oxynitride (SiOxNy) [J. Micro. Manuf.1 , 20180102 (2018)], or by converting SiO2 to SiOxNy, presented in this paper. We computationally demonstrate the feasibility of a nitridation-etch process for SiO2 in fluorocarbon/nitrogen-based plasma with molecular dynamics (MD) and quantum chemistry (QC) simulations. First, the nitridation via ion implantation is observed with MD, which replaces surface oxygen by nitrogen. Second, the reactions involving oxygen and silicon volatilization are energetically favorable per QC calculations. Finally, both MD and QC simulations indicate a synergy between fluorine and nitrogen etchants by enhancing each other’s reactivity with the SiO2 surface. These atomistic surface reaction mechanisms will offer insight for the development of robust engineering solutions for 3D-NAND fabrication.